Cross-border activity in the Kent - Nord-Pas de Calais - Belgium Euroregion: some comparative evidence on the location and recruitment decisions of internationally mobile firms - William Collier; Roger Vickerman (European Regional Science Association (ERSA), 2002)
Border regions and the implications for their development have become a subject of considerable interest in the ongoing process of European integration. The removal of national barriers and the development of greater economic and political transborder co-operation has led to a reconsideration of spatial identity and the definition of regional economies or markets. Much of the interest has focussed on the implications for labour mobility, especially within the context of the perceived need for greater mobility to provide the necessary adjustment process within the Eurozone. However, not only has international labour migration remained quite low within the EU, so has the level of cross-border commuting. There has, however, been considerable interest in the growth of cross-border capital flows. In this paper we explore the nature of this cross-border movement of firms in the context of the Kent - Nord-Pas de Calais - Belgium Euroregion. This transnational region is a large region of over 15 million people, close to a number of national borders. The original focus was the Transmanche region between Kent and Nord-Pas de Calais, established in relation to the construction of the Channel Tunnel in1987 in order to identify common problems, minimise the competition for the same resources between the regions and emphasise complementarity in their economic structures. The region was later extended to include the three Belgian regions in 1991 when it was renamed the Euroregion, and there have been suggestions that it should extend even more widely to include most or all of the Central Capitals Region of the EU. This paper brings together some findings from a survey of French firms which have located in Kent and a parallel survey of Belgian firms which have located in the Dunkerque employment area of Nord-Pas de Calais (Boutillier et al, 2001). In this analysis we seek to discover whether the same general set of principles govern cross-border movements, or whether there are individual circumstances in each region to which specific types of firm respond. Despite similarities, it is difficult to conclude that there is a consistent pattern of cross-border investment activity. As with all investment activity, cross-border investment seeks to exploit differentials which exist and opportunities which arise; these are different in different cases. Belgian activity in the Dunkerque region is responding to clear advantages which are offered through location in an area where incentives are strong and where there are specific skills which can be used to advantage. French investment in Kent seems to be responding to wider national opportunities available in the UK, but using a location which has certain advantages of proximity. It would seem unwise to rely on either of these factors as being likely to persist indefinitely. By definition firms which have been willing to move in will also find it relatively easy to move on to other locations, possibly to other regions within the host country. In this sense border regions continue to act as staging posts for mobile factors and thus have to recognise the need for continuing activity to attract new firms and retain existing ones.
Keywords: 330